2015
DOI: 10.1007/s00264-015-2898-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination of low-intensity pulsed ultrasound and C3H10T1/2 cells promotes bone-defect healing

Abstract: LIPUS treatment effectively promotes C3H10T1/2 cells to enter the growth/split phase from the stationary phase. This process enhances cell proliferation, which consequently promotes bone-defect healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…27,30,31 Mesenchymal stem cells have been claimed to have the ability to sense and respond to physical stimuli. 32,33 Several preliminary studies have suggested that LIPUS can act on MSCs and promote their proliferation in vitro, [34][35][36] while some other studies have reported that LIPUS has no effect on or even inhibits the proliferation of stem cells. [37][38][39] It has been reported that p44/p42 extracellular signal-regulated kinases (ERK1/2) signalling pathway can be activated by various mechanical stimuli, 40 and they are crucial signalling molecules in LIPUS-induced cellular responses.…”
Section: Human Amnion-derived Mesenchymal Stem Cells (Had-mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…27,30,31 Mesenchymal stem cells have been claimed to have the ability to sense and respond to physical stimuli. 32,33 Several preliminary studies have suggested that LIPUS can act on MSCs and promote their proliferation in vitro, [34][35][36] while some other studies have reported that LIPUS has no effect on or even inhibits the proliferation of stem cells. [37][38][39] It has been reported that p44/p42 extracellular signal-regulated kinases (ERK1/2) signalling pathway can be activated by various mechanical stimuli, 40 and they are crucial signalling molecules in LIPUS-induced cellular responses.…”
Section: Human Amnion-derived Mesenchymal Stem Cells (Had-mscs)mentioning
confidence: 99%
“…Mesenchymal stem cells have been claimed to have the ability to sense and respond to physical stimuli . Several preliminary studies have suggested that LIPUS can act on MSCs and promote their proliferation in vitro , while some other studies have reported that LIPUS has no effect on or even inhibits the proliferation of stem cells …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we chose a lower frequency of LIPUS so that its energy could pass through the bone tissue and act on the bone marrow. In a previous study, the temporal and spatial average of acoustic intensity of 30‐mW/cm 2 LIPUS showed a good proliferative effect on BMSCs. Therefore, a preliminary mathematical simulation was performed to estimate whether 30 to 100 mW/cm 2 of energy could reach bone marrow after the US passed through the skin, soft tissue, and cortical bone.…”
Section: Discussionmentioning
confidence: 81%
“…Bone marrow mesenchymal stem cells (BMSCs) and the osteoblasts and endothelial cells differentiated from BMSCs are important components of the hematopoietic microenvironment, providing nutrition and structural support for the normal proliferation and differentiation of hematopoietic stem cells and playing a key regulatory role. Our early study showed that low‐intensity pulsed ultrasound (LIPUS) could promote the proliferation of BMSCs and accelerate the differentiation of BMSCs into osteoblasts and endothelial cells (our unpublished data, 2016). Therefore, we hypothesize that LIPUS could promote the proliferation and differentiation of BMSCs in the bone marrow by acting on the bone marrow, thereby affecting the hematopoietic microenvironment, modulating the hematopoietic function of hematopoietic stem cells, and eventually alleviating myelosuppression.…”
mentioning
confidence: 99%
“…Based on previous studies [25,26] and our pilot experiment, the cells in the LIPUS treated groups (LC, LO, LV and LD) were treated with low-intensity pulsed ultrasound (Chongqing Haifu Medical Technology Co., Ltd., Chongqing, China), setting the frequency at 0.6 MHz, repeat frequency at 1 kHz, duty cycle at 20% and intensity at 30 mW/cm 2 . The cells were exposed to 30 mW/cm 2 treatment for 20 min everyday and for 13 consecutive days.…”
Section: Lipus Treatmentmentioning
confidence: 99%